2013
DOI: 10.1073/pnas.1303004110
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-8A binds to and regulates Raf-1 kinase

Abstract: V-raf-1 murine leukemia viral oncogene homolog 1 (Raf-1) is a key activator of the ERK pathway and is a target for cross-regulation of this pathway by the cAMP signaling system. The cAMP-activated protein kinase, PKA, inhibits Raf-1 by phosphorylation on S259. Here, we show that the cAMP-degrading phosphodiesterase-8A (PDE8A) associates with Raf-1 to protect it from inhibitory phosphorylation by PKA, thereby enhancing Raf-1's ability to stimulate ERK signaling. PDE8A binds to Raf-1 with high (picomolar) affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 48 publications
4
68
0
Order By: Relevance
“…Critically, this biochemical interaction was shown to be relevant to oxidative stress tolerance in the organism, especially given the putative localisation of PDE8 in mitochondria as well as the role of the tubules in stress resistance. PDE8 deletion mutants are significantly more susceptible to oxidative stress imposed by either H 2 O 2 or paraquat feeding, compared with parental controls (Brown et al, 2013). This work demonstrates for the first time in insects that cAMP and ERK signalling mediates oxidative stress tolerance.…”
Section: Signalling Mechanisms In Oxidative Stress Tolerancementioning
confidence: 68%
See 2 more Smart Citations
“…Critically, this biochemical interaction was shown to be relevant to oxidative stress tolerance in the organism, especially given the putative localisation of PDE8 in mitochondria as well as the role of the tubules in stress resistance. PDE8 deletion mutants are significantly more susceptible to oxidative stress imposed by either H 2 O 2 or paraquat feeding, compared with parental controls (Brown et al, 2013). This work demonstrates for the first time in insects that cAMP and ERK signalling mediates oxidative stress tolerance.…”
Section: Signalling Mechanisms In Oxidative Stress Tolerancementioning
confidence: 68%
“…The PDE8A isoform is localised to mitochondria (Tsai and Beavo, 2011), and in D. melanogaster, DmPDE8 is the orthologue of mammalian PDE8A (Davies and Day, 2007). In a recent study, PDE8A was shown to have a novel binding partner, Raf-1, which allows modulation of downstream extracellular signal-regulated kinase (ERK) signalling via phosphorylation of ERK by Raf-1 kinase (Brown et al, 2013). DmPDE8 is abundantly expressed in epithelia, including the tubules, and PDE8 deletion mutants show reduced phospho-ERK signals.…”
Section: Signalling Mechanisms In Oxidative Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Of import, this system was shown to be operational and to control basal Raf-1-mediated phosphorylation of ERK when tested in wild-type and PDE8-null Drosophila, as well as in Leydig cells isolated from wild-type and PDE8-null mice. Although previous studies have shown that PDE3-or PDE4-family enzymes can be counted on to control localized cAMPdependent events in cells (8-12), Brown et al's study (3) shows that local control of Raf-1 activity can be added to the list of important signaling events that are regulated in cells by the hyperlocalized hydrolysis of cAMP by compartmented PDEs.…”
mentioning
confidence: 99%
“…Using several complementary approaches, including peptide array-based binding studies, Brown et al (3) demonstrate that Raf-1 and PDE8A interact directly without the need of accessory proteins or lipids, and identify a peptide motif in PDE8A (R454 RLSGNEY461) critical for this interaction. Interestingly, although the affinity of many protein-protein interactions tends to be weak, in this instance PDE8A/Raf-1 binding was very tight (K d < 61 pM), and was not affected by changes in cellular cAMP concentrations or the presence in cells of PDE8 cAMP Fig.…”
mentioning
confidence: 99%